A shortened whole brain radiation therapy protocol for meningoencephalitis of unknown origin in dogs - Herzig, Robert; Beckmann, Katrin; Körner, Maximilian; Steffen, Frank; Rohrer Bley, Carla (Frontiers in Veterinary Science, 2023)
A variety of treatment options have been described for canine meningoencephalitis of unknown origin (MUO). Only few studies focused on radiation therapy as a second line immunomodulating treatment, implicating its effective use including in MUO, even in dogs refractory to medical therapy. However, a standard radiation therapy protocol is lacking, and further research will help to evaluate the effect of different dose regimens. Ten dogs (two with focal and eight with multifocal intracranial lesions) diagnosed with MUO based an MRI and CSF findings were prospectively enrolled to evaluate the efficacy of a shortened whole brain radiation therapy protocol (5 x 4 Gy) in combination with prednisolone. Seven dogs were diagnosed de novo and 3 had a history of relapsing MUO. Neurological status improved in all 10 dogs during radiation therapy, with 4 out of 10 returning to normal shortly after radiation therapy. Additionally, 2 dogs showed a full recovery within 3 months after radiation therapy. Two dogs suffering from epileptic cluster seizures became seizure-free after radiation therapy. Three dogs died within the first 3 months after radiation therapy, one of them with a confirmed relapse. In the remaining 7 dogs, follow-up MRI and CSF examination was performed after 3-5 months. On follow-up MRI lesions completely resolved in 2 dogs, partially resolved in 5 dogs and progressed in 1 dog. After follow-up MRI, dogs were further treated with prednisolone monotherapy (2 dogs) and second line immunosuppressive drug; ciclosporin (4 dogs) and mycophenolate-mofetil (1 dog) in conjunction with prednisolone. Overall, 4 dogs showed disease progression, with a mean time to progression of 691 days (95%CI: 396-987) and mean overall survival for all dogs was 723 days (95%CI: 436-1011), (both medians not reached). Shortened whole-brain radiation therapy could be an additional treatment option for MUO in conjunction to prednisolone, specifically for cases that require rapid relief of symptoms and with relapsing history.